Crop Domestication, Root Trait Syndromes, and Soil Nutrient Acquisition in Organic Agroecosystems: A Systematic Review - Isaac, Marney E.; Nimmo, Victoria; Gaudin, Amélie C. M.; Leptin, Andrea; Schmidt, Jennifer Elise; Kallenbach, Cynthia M.; Martin, Adam; Entz, Martin; Carkner, Michelle; Rajcan, Istvan; Boyle, T. D.; Lu, Xin (Frontiers in Sustainable Food Systems, 2021)
Selecting crops that express certain reproductive, leaf, and root traits has formed detectable, albeit diverse, crop domestication syndromes. However, scientific and informal on-farm research has primarily focused on understanding and managing linkages between only certain domestication traits and yield. There is strong evidence suggesting that functional traits can be used to hypothesize and detect trade-offs, constraints, and synergies among crop yield and other aspects of crop biology and agroecosystem function. Comparisons in the functional traits of crops vs. wild plants has emerged as a critical avenue that has helped inform a better understanding of how plant domestication has reshaped relationships among yield and traits. For instance, recent research has shown domestication has led important economic crops to express extreme functional trait values among plants globally, with potentially major implications for yield stability, nutrient acquisition strategies, and the success of ecological nutrient management. Here, we present an evidence synthesis of domestication effects on crop root functional traits, and their hypothesized impact on nutrient acquisition strategies in organic and low input agroecosystems. Drawing on global trait databases and published datasets, we show detectable shifts in root trait strategies with domestication. Relationships between domestication syndromes in root traits and nutrient acquisition strategies in low input systems underscores the need for a shift in breeding paradigms for organic agriculture. This is increasingly important given efforts to achieve Sustainable Development Goal (SDG) targets of Zero Hunger via resilient agriculture practices such as ecological nutrient management and maintenance of genetic diversity.